PENINGKATAN KEMAMPUAN KOGNITIF ANAK MELALUI STEAM DENGAN COOKING CLASS - Wini Agustina; Feri Faila Sufa; M. Hery Yuli Setiawan (Widya Wacana: Jurnal Ilmiah, 2022)
This study aims to determine the increase in children's cognitive abilities through Steam with Cooking Class at KB Aisyiyah Al-Amin Bibis Luhur Surakarta Academic Year 2022/2023. This research is Classroom Action Research using quantitative descriptive data analysis techniques, data collection techniques using observation, interviews, and documentation. The results of the study show that STEAM activities with Cooking Class can improve children's cognitive abilities at the Aisyiyah Al-Amin Bibis Luhur Surakarta KB. This can be proven by the level of cognitive development of children who are developing very well. In cycle I, children's cognitive development experienced an increase of 50% in the criteria of developing as expected. Whereas in cycle II, children's cognitive development increased by 88.88% in the criteria of developing as expected. This research was banned in cycle II because it met the indicator success criteria, namely ≥80%. Based on this research, it can be concluded that Steam activities with Cooking Class can improve children's cognitive abilities at the Aisyiyah Al-Amin KB.